(untitled) (Research, Society and Development, 2022)
The supervised internship is the union of theoretical and practical knowledge as a way of developing skills for working in the professional field. Thus, the present study aims to describe the perception of students from the Instituto Educacional Santa Catarina- Faculdade Guaraí (IESC-FAG) in the health area about supervised internships. This is a descriptive research, with quantitative analysis. Analyzing the 82 responses obtained through the online questionnaire, it is clear that most of the participants did not feel completely prepared for the beginning of the supervised internships, where they felt nervous and anxious for the moment. However, the questioning about the indispensability of the internship occurred with predominance among them. With this, the research results were very diversified, since the academics of the different courses gave different answers through positive and/or negative points, where it is observed that supervised internships are indispensable, so that there is the best use of professional practice.